HUBUNGAN SELF-CARE MANAGEMENT DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD BANDUNG KIWARI TAHUN 2025 - Hermawan, Syifa Putri; B, Rustandi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Chronic kidney failure is a clinical problem caused by decreased kidney function. Hemodialysis is a procedure to replace kidney function, long-term hemodialysis can reduce the quality of life of patients. Self-care management is needed to ensure that treatment is carried out properly. This study aims to analyze the relationship between self-care management and the quality of life of chronic kidney failure patients undergoing hemodialysis. This type of research is a quantitative research that is correlational with a cross-sectional approach. Sampling uses a total sampling technique with a sample of 40 people. Data analysis using the chi square test to determine the relationship, the results obtained A total of 27 respondents have self-care management in the good category and 21 respondents have a quality of life in the good category. There is a significant relationship between self-care management and quality of life in chronic kidney failure patients undergoing hemodialysis with a p-value <0.001. There is a relationship between self-care management and quality of life in chronic kidney failure patients undergoing hemodialysis.